Awareness of Venous Thromboembolism in Patients With Cancer and Their Carers: Protocol for Systematic Review - Ann‐Rong Yan; Gregory M. Peterson; Mark Naunton; Phillip Newman; Murray R. Turner; Desmond Yip; Nasser Bagheri; Reza Mortazavi (Thoracic Cancer)
ABSTRACT Background There is an increased risk of venous thromboembolism (VTE) for people living with cancer. However, the awareness of VTE in this population or their carers appears to be low. This lack of awareness may lead to poor outcomes, such as VTE due to low adherence to thromboprophylaxis or delayed hospital presentations with neglected VTE symptoms. This study protocol will guide researchers in conducting a systematic review of existing studies (quantitative, qualitative, or mixed methods) which have assessed VTE awareness among patients living with cancer or their carers. It will also investigate the rates and predictors of VTE awareness in those populations. Methods This protocol was designed following the PRISMA‐P 2015 statement and the methodological guidance from the PRISMA 2020 statement. Six databases (APA PsycINFO, CINAHL, Google Scholar, Medline, Scopus, and Web of Science Core Collection) will be searched to retrieve all eligible studies. Covidence software will be utilized to assist in the screening of studies for eligibility. A standard data extraction form will be used, and the Mixed Methods Appraisal Tool (MMAT) will be used to assess the methodological quality of each included study. Both a qualitative descriptive approach and meta‐analysis will be used for data synthesis and integration where possible. The protocol has been registered with PROSPERO (CRD42025628429).